Geomorphological mapping: methods and applications - Smith, Mike J. (Developments in earth surface processes, 2011)
Front Cover -- Geomorphological Mapping -- Copyright Page -- Contents -- Foreword -- List of Contributors -- 1: Geomorphological Mapping -- 1. Introduction to Applied Geomorphological Mapping -- 1. Geomorphological Mapping -- 2. Techniques of Applied Geomorphological Mapping -- 3. Case Studies in Applied Geomorphological Mapping -- References -- 2. Old and New Trends in Geomorphological and Landform Mapping -- 1. The Advent of Geomorphological Mapping -- 2. The Diversity of Legends -- 3. The Needs for Standardisation and Flexibility -- 4. The Use of Aerial Photographs and Satellite Data -- 5. Landform Mapping in Synthetic (Holistic) Surveys of Terrain -- 6. Applied Geomorphological Surveying and Mapping -- 7. Summary and Conclusions -- References -- 3. Nature and Aims of Geomorphological Mapping -- 1. Introduction -- 2. Types of Geomorphological Maps -- 3. Geomorphological Map Scale -- 3.1 Large-Scale Geomorphological Maps -- 3.2 Medium-Scale Geomorphological Maps -- 3.3 Small-Scale Geomorphological Maps -- 4. New Tools in Geomorphological Mapping -- 4.1 Global Positioning System -- 4.2 Satellite Imagery -- 4.3 Digital Elevation Models -- 4.4 Geographical Information System -- 5. Problems and Efforts in Current Geomorphological Mapping -- 5.1 Interoperability -- 5.2 Hierarchical Taxonomy and Multiscale Geomorphological Mapping -- 5.3 Full-Coverage Object-Oriented Mapping -- 6. Experiences of GIS-Based, Object-Oriented Multiscale Geomorphological Mapping -- 7. Concluding Remarks -- References -- 4. Makers and Users of Geomorphological Maps -- 1. Introduction -- 2. Geomorphological Mapping Characteristics -- 3. Makers and Users -- 4. Examples of Nationwide Map Makers -- 4.1 Germany -- 4.2 Spain -- 4.3 The Netherlands -- 4.4 Italy -- 4.5 Romania -- 4.6 Australia -- 4.7 China -- 4.8 Brazil -- 5. Users.
Includes bibliographical references and index. - Description based on print version record
Keywords: Aufsatzsammlung; Geomorphologische Kartierung